Off-pump total arterial bypass grafting for the elderly does not improve life expectancy - Nuttapon Arayawudhikul; Ryohei Ushioda; Ryohei Ushioda; Hideki Isa; Hideki Isa; Dit Yoongtong; Boonsap Sakboon; Jaroen Cheewinmethasiri; Thanin Lokeskrawee; Jayanton Patumanond; Suppachai Lawanaskol; Hiroyuki Kamiya (Frontiers in Cardiovascular Medicine)
ObjectivesTo assess whether total arterial revascularization (TAR) offers survival and freedom from major adverse cardiac or cerebrovascular events (MACCE) benefit in elderly patients with multivessel coronary artery disease undergoing off-pump coronary artery bypass grafting (OPCAB), as compared to using a single internal thoracic artery (ITA) with additional saphenous vein graft (SVG).MethodsWe retrospectively analyzed 598 patients aged >70 years who underwent coronary revascularization from August 2017–July 2023. After excluding high-risk patients and those with SVG plus more than two arterial grafts, 428 patients remained (101, TAR group; 327, single ITA + SVG group). A propensity score was used to create the TAR and single ITA + SVG groups with 1:1 ratio (100 patients in each group). Moreover, matching was performed based on eight covariates with preoperative clinical characteristics.ResultsThe unmatched cohort had 70 (69.3%) and 178 (54.4%) men in the TAR and ITA + SVG groups, respectively (mean age, 74.1 ± 3.5 and 75.2 ± 4.2 years, respectively). After matching, both groups had similar demographics. The survival (p = 0.410) and MACCE-free rates (p = 0.494) over 5 years were not significantly different between the two groups. Univariable analysis showed that TAR [hazard ratio (HR) = 0.74, 95% confidence interval (CI) = 0.44–1.22, p = 0.233] and complete revascularization (HR = 0.61, 95%CI = 0.34–1.09, p = 0.094) were not significant risk factors for long-term mortality.ConclusionElderly patients who underwent OPCAB with total arterial grafting did not show survival or free-MACCE benefits for over 5 years.